Accuracy of Budgeting Plan and Expenditure Realization in the Mining Industry - Firmansyah; Ahmad Juanda; Driana Leniwati (Dinasti Publisher, 2025)
This research discusses the accuracy of budgeting plans and the realization of expenditures in the mining industry, which is a crucial aspect of financial management for companies. The method used is descriptive qualitative analysis to evaluate the comparison between budget plans and actual expenditures, focusing on identifying factors that influence budget accuracy. The results indicate that precision in budget planning significantly impacts operational efficiency and company profitability, despite challenges such as commodity price fluctuations, regulatory changes, and market uncertainties that can affect expenditure realization. This study emphasizes the importance of regular budget monitoring and adjustments, as well as the implementation of effective risk management practices to achieve desired financial objectives. Consequently, this research provides recommendations for mining companies to enhance budgeting accuracy and financial management for operational sustainability.